Rare form of cherubism: Case report with review of literature - Sudhaa Mani; Balan Natarajan; Karthik Rajaram; Yasmeen Ahmed Sahuthullah; Subramanium Gokulanathan; Govindasamy Sitra (Wolters Kluwer Medknow Publications, 2013)
Cherubism was first described by Jones in 1933 as "familial multilocular cystic disease of jaws." Renamed as cherubism in 1938 because of classical characteristics of full round cheeks and upward cast of the eyes to the angelic look of the cherubs immortalized by renaissance art. It is characterized by progressive painless bilateral swelling of jaws involving either maxilla or mandible producing chubby face. It is uncommon fibro-osseous disorder of bone. Mutation in the gene encoding SH3-binding protein 2 (SH3BP2) plays a role in the disease. There are indications that the gene SH3BP2 plays a role in regulating the increased osteoblast and osteoclast activities that are seen in normal tooth eruption and point mutations in the gene could cause pathologic activation of osteoclasts. The purpose of this paper is to present the uncommon form of cherubism and to review the clinicoradiographic, histopathologic features and treatment so as to facilitate diagnosis of disease.